Stimulator of interferon genes defends against bacterial infection via IKKβ-mediated Relish activation in shrimp - Li, Haoyang; Li, Qinyao; Wang, Sheng; He, Jianguo; Li, Chaozheng (Frontiers in Immunology, 2022)
Stimulator of interferon genes (STING) is crucial for the innate immune to defend against pathogenic infections. Our previous study showed that a STING homolog from Litopenaeus vannamei (LvSTING) was involved in antibacterial response via regulating antimicrobial peptides (AMPs). Nevertheless, how LvSTING induces AMPs expression to inhibit bacterial infection remains unknown. Herein, we revealed that the existence of a STING–IKKβ–Relish–AMPs axis in shrimp that was essential for opposing to Vibrio parahaemolyticus invasion. We observed that LvRelish was essential for host defense against V. parahaemolyticus infection via inducing several AMPs, such as LvALF1, LvCRU1, LvLYZ1 and LvPEN4. Knockdown of LvSTING or LvIKKβ in vivo led to the attenuated phosphorylation and diminished nuclear translocation of LvRelish, as well as the impaired expression levels of LvRelish-regulated AMPs. Accordingly, shrimps with knockdown of LvSTING or LvIKKβ or both were vulnerable to V. parahaemolyticus infection. Finally, LvSTING could recruit LvRelish and LvIKKβ to form a complex, which synergistically induced the promoter activity of several AMPs in vitro. Taken together, our results demonstrated that the shrimp STING–IKKβ–Relish–AMPs axis played a critical role in the defense against bacterial infection, and provided some insights into the development of disease prevention strategies in shrimp culture.